2011
DOI: 10.1007/s00726-011-0879-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new functionalized aziridine-2- and azetidine-3-carboxylic acid derivatives of potential interest for biological and foldameric applications

Abstract: A short synthesis of alkyl 2-(bromomethyl)aziridine-2-carboxylates and alkyl 3-bromoazetidine-3-carboxylates was developed involving amination, bromination and base-induced cyclization of alkyl 2-(bromomethyl)acrylates. The aziridines are the kinetically favored cyclization products and could be transformed into 3-bromoazetidine-3-carboxylic acid derivatives via thermal isomerization. The new small-membered azaheterocyclic α-and β-amino acid derivatives contain a bromo-substituted carbon center as a useful moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…To demonstrate the usefulness of the synthesized constrained C α ‐tetrasubstituted amino acid derivative 20 as a possible building block for the synthesis of peptides, it was subjected to hydrogenolysis and hydrolysis reactions 1c,21. The hydrogenolysis of 3‐azidoazetidine 20 by using 10 wt.‐% palladium on carbon in ethanol at room temperature for 30 min afforded ethyl 1‐tosyl‐3‐aminoazetidine‐3‐carboxylate ( 22 ) in 83 % yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the usefulness of the synthesized constrained C α ‐tetrasubstituted amino acid derivative 20 as a possible building block for the synthesis of peptides, it was subjected to hydrogenolysis and hydrolysis reactions 1c,21. The hydrogenolysis of 3‐azidoazetidine 20 by using 10 wt.‐% palladium on carbon in ethanol at room temperature for 30 min afforded ethyl 1‐tosyl‐3‐aminoazetidine‐3‐carboxylate ( 22 ) in 83 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our research group reported the synthesis of azetidines 5 , which are heterocyclic analogues of amino acid 4 and have an electron‐donating alkyl group at the azetidine nitrogen atom (Figure 3). 1c A subsequent investigation of the conformational features of these amino acid analogues in model peptides 6 and 7 led us to conclude that such a 3‐aminoazetidine‐3‐carboxylic acid moiety is a β‐turn inducer 21…”
Section: Introductionmentioning
confidence: 99%
“…Additional support for the occurrence of different isomeric cations has been provided by the ring expansion of 2‐(bromomethyl)aziridines 42 to the corresponding 3‐substituted azetidines 46 . In that study, the isomerization reaction of alkyl aziridine‐2‐carboxylates 42 to alkyl azetidine‐3‐carboxylates 45 has been investigated (Scheme ).…”
Section: Preparation and Synthetic Utilization Of Bicyclic Aziridinimentioning
confidence: 99%
“…Best results in terms of yield was obtained via dropwise addition of Tf 2 O to a premixed solution of (R)-1,3-butanediol 14 and Hunig's base at À35 C followed by treatment with benzhydrylamine resulted in the formation of 18 which upon hydrogenolysis in the presence of palladium hydroxide to afford (S)-2-methylazetidine(R)-(À)-camphorsulfonate (CSA) 17 (Scheme 5). 10 De Kimpe and co-workers 11 have developed thermal isomerization of aziridines for the synthesis of 3-bromoazetidine-3-carboxylic acid derivatives. The key step involved the base promoted cyclization of dibromo amino esters 21 to yield the desired aziridines 22 and/or azetidines 23.…”
Section: Introductionmentioning
confidence: 99%
“…with Pd/C yielded the corresponding 3-aminoazetidine-3carboxylate 26 (Scheme 6). 11 The above methodology was further extended by De Kimpe and co-workers 14 to afford a facile access to 1-t-butyl-and 1-(4methylbenzyl)-3-bromo-3-methylazetidines as shown in Scheme 7. The synthetic approach followed a sequence of synthetic events with the key step involving the thermal isomerisation of aziridine 30 in acetonitrile to afford 3-bromoazetidine 31 (Path A).…”
Section: Introductionmentioning
confidence: 99%